Pengaruh Capital Expenditure, Profitabilitas, Leverage, Dan Corporate Social Responsibility Disclosure Disclosure Terhadap Kinerja Keuangan (Studi Kasus Pada Perusahaan Manufaktur Yang Terdaftar Di BEI Tahun 2017-2019) - Rif’a Maulana; Rois Arifin; Budi Wahono (UNIVERSITAS ISLAM MALANG, 2021)
AbstractThis study aims the effect of capital expenditure, profitability, leverage, and corporate social responsibility disclosure on the financial performance of case studies in manufacturing companies listed on the Indonesia Stock Exchange in 2017-2019. In this study, there are 4 (four) independent variables used to measure the capital adequacy ratio, namely capital expenditure, profitability, leverage, and corporate social responsibility disclosure. And the dependent variable in this study is financial performance. The population in this study were all manufacturing companies listed on the Indonesia Stock Exchange for the 2017-2019 period with a total of 193 manufacturing companies and the samples in this study were taken using a purposive sampling technique, namely the selection of sample members based on certain criteria and obtained a sample of 95 manufacturing companies. The data collection method used is the documentation method, namely by recording or documenting the data listed in the annual report at (IDX). The data analysis technique used in this research is multiple linear regression. The results of the study state that simultaneously capital expenditure, profitability, leverage, and corporate social responsibility disclosure have a positive and significant effect on financial performance. Partially, capital expenditure, profitability, and corporate social responsibility disclosure have a positive and significant effect on financial performance. Leverage has a negative and significant effect on financial performance. Keywords: capital expenditure, profitability, leverage, and corporate social Responsibility disclosure, financial performance